If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13/9+x=3
We move all terms to the left:
13/9+x-(3)=0
determiningTheFunctionDomain x-3+13/9=0
We multiply all the terms by the denominator
x*9+13-3*9=0
We add all the numbers together, and all the variables
x*9-14=0
Wy multiply elements
9x-14=0
We move all terms containing x to the left, all other terms to the right
9x=14
x=14/9
x=1+5/9
| 15=80*3.5^x | | -26=4×-3x | | 5a-6+5(a-10)=24 | | 9(3x-3)=18 | | 8x=11=51 | | -6-(-3)=3t+3 | | 11x=8=51 | | -2.666+2x=-4.666 | | 12x13=13 | | -6–3=3t+3 | | 4-3x=-1-2x | | ((10^(3x))=17 | | 11+5x=60+2x | | (x+20)+40+(2x-30)=180 | | -16+6k=6(k-3) | | (x-20)+(x-60)+(x-40)+130+120+110=720 | | 5x-15=8x+11 | | a+5=a-7 | | a+1/2=-3/2 | | 14/9+x=3 | | -22/3+2x=-42/3 | | 5=(2x+11) | | a+1/2=-11/2 | | n-12=49 | | 2x+41/15=9 | | 14x+18=6x+210 | | 12=(3.14)d | | -2(x+5)+108=16+32 | | 225+5x=10x | | 22=(3y+10) | | 3+6x=5x+6 | | 5x+225=10x |